Clinical efficacy of Shugan granule in the treatment of mixed anxiety-depressive disorder: A multicenter, randomized, double-blind, placebo-controlled trial. (23rd May 2022) - Li, Yang; Li, Liqi; Guo, Rongjuan; Yu, Hua; Wang, Xinping; Wang, Baoshen; Wang, Qiufeng; Li, Zengxiang; Zhao, Huixin; Temu, Qile; Chen, Xiaochun; Zhang, Yurong; et al.
Abstract: Ethnopharmacological relevance: Shugan granule is derived from Xiaoyao powder, a traditional Chinese medicine that has been shown to be effective in treating emotional disorders. At present, there is no standard drug treatment for mixed anxiety-depressive disorder (MADD), and no evidence-based clinical trial has been performed for any drug, meaning MADD patients are unable to obtain standardized treatment. Aim of the study: The purpose of this clinical trial was to test the clinical efficacy and safety of Shugan granules in the treatment of MADD, and to provide clinical trial-based support along with drug recommendations for the treatment of MADD. Materials and methods: A multicenter, randomized, double-blind, placebo-controlled study was conducted on 400 patients with MADD recruited from January 1, 2019 to December 31, 2020, and they were randomly divided into test and placebo groups with a 1:1 ratio. Subjects in the test group (n = 200) received oral administration of Shugan granules, while subjects in the placebo group (n = 200) received oral administration of a Shugan granule simulator. The treatment lasted for 8 weeks. The Hamilton Anxiety Scale (HAMA), Hamilton Depression Scale-17 (HAMD-17), Clinical Global Impression Scale (CGIS), Self-rating Anxiety Scale (SAS), and Self-rating Depression Scale (SDS) were used to evaluate efficacy. In addition, the traditional Chinese medicine (TCM) syndrome scale for MADD was developed to observe improvements of related symptoms in patients after treatment based on the disease guidelines of TCM and the clinical manifestations of depression. Furthermore, the safety of Shugan granules was evaluated during and after treatment. Results: After 8 weeks of treatment, the total scores for HAMA, HAMD, SAS, and SDS in the test group were significantly lower than those in the placebo group (P < 0.01). The proportion of patients with efficacy index (EI) > 1 for the CGIS score in the test group was significantly higher than that in the placebo group (P < 0.01). The efficacy of treatment in the test group based on the TCM syndrome scale was 70.16% and 88.27% after 4 weeks and 8 weeks, respectively, which was significantly higher than that in the placebo group (44.27% and 66.67% after 4 weeks and 8 weeks, respectively; P < 0.01). The disappearance rate of single symptoms in the test group was 20–30% higher than that in the placebo group, with a significant difference between groups (P < 0.05). During the treatment period, the incidence of adverse reactions was 2.05% in the test group and 2.06% in the placebo group, with no significant differences noted (P = 1.0000). Conclusion: Shugan granule was more effective than placebo in the treatment of MADD. Moreover, there was no significant difference between the two groups in terms of safety. This paper provides a clinical therapeutic regime using Shugan granule for the treatment of MADD. Graphical abstract: Image 1 Highlights: As far as we know, this is the first randomized controlled multicenter clinical trial for MADD in the world. The indications for usage of Xiaoyao powder was expanded to the treatment or control of MADD. We developed the TCM symptom scale for evaluation of MADD and therapeutic effects of medications on it. This study provides a high-quality evidence for the treatment of MADD by using a standardized traditional formula".